2018
DOI: 10.3390/cryst8020075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, Herbicide Safening, and Antifungal Activity of N-(4,6-Dichloropyrimidine-2-Yl)Benzamide

Abstract: Abstract:The compound N-(4,6-dichloropyrimidine-2-yl)benzamide (C 11 H 7 Cl 2 N 3 O) was synthesized and the corresponding structure was confirmed by 1 H NMR, 13 C NMR, HRMS, IR, and single-crystal X-ray diffraction. The compound crystallized in a monoclinic system with space group P 2 1 /c, where a = 14.9156(6), b = 16.6291(8), c = 14.4740(6) Å, β = 95.160(2) • , V = 3575.5(3) Å 3 , Z = 12, Dc = 1.494 g·cm −3 , F(000) = 1632, µ(MoKa) = 3.182 mm −1 , final R = 0.0870, and wR = 0.2331 with I > 2σ(I). The crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…The phytotoxicity of compounds a-u on rice and the herbicide safening activities of SA and 20 substituted SA compounds (a-u) were evaluated by agar culture methodology under laboratory conditions according to a previous method [42]. A 12 g agar strip was added to 3 L of deionized water at 100 • C. The mixture was then constantly stirred over heat until the agar strip had completely dissolved.…”
Section: Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phytotoxicity of compounds a-u on rice and the herbicide safening activities of SA and 20 substituted SA compounds (a-u) were evaluated by agar culture methodology under laboratory conditions according to a previous method [42]. A 12 g agar strip was added to 3 L of deionized water at 100 • C. The mixture was then constantly stirred over heat until the agar strip had completely dissolved.…”
Section: Growth Conditionsmentioning
confidence: 99%
“…Agar media were as follows: 0.25 µM M; 8 mg L −1 of compounds a-u; 8 mg L −1 F with 0.25 µM M; 8 mg L −1 compounds a-u with 0.25 µM M; and no additional compounds. Seedlings were collected and planted according to previous methods [41,42]. Fifty seedlings were added to each plastic box and incubated for 14 h at 30 • C under a grow light (intensity 110-130 µE m -2 s −1 ), followed by a 10 h dark photoperiod at 25 • C. After 7 days, indexes related to herbicide safener activity (plant height, root length, and fresh weight) of the seedlings in each box were measured.…”
Section: Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The great number of heterocyclic compounds is used in medicine as drugs for miscellaneous diseases. The drugs that have the heterocyclic core in their frame have some specific activity such as antifungal activity, anti‐inflammation, antibacterial, antioxidants, anticonvulsant, antiallergic, herbicidal activity, and and anticancer …”
Section: Introductionmentioning
confidence: 99%
“…The great number of heterocyclic compounds is used in medicine as drugs for miscellaneous diseases. The drugs that have the heterocyclic core in their frame have some specific activity such as antifungal activity, 46 anti-inflammation, 47 antibacterial, 48 antioxidants, 49 anticonvulsant, 50 antiallergic, 51 herbicidal activity, 52 and and anticancer. 49 Although a number of studies have been reported on bioactivity of ferrocene and xanthone individually, 1-6,44,53-55 based on our knowledge, there is still no report on anticancer polymers bearing ferrocene and xanthone in the main chain.…”
mentioning
confidence: 99%